Dietary supplementation with vitamin C ameliorates the adverse effects of Salmonella Enteritidis-challenge in broilers by shaping intestinal microbiota - Liping Gan (Poultry Science, 2020)
Salmonella Enteritidis (SE) infection is not only a leading cause of poor production performance and compromised animal welfare in broilers but also a potential threat to public health. Two experiments were conducted to evaluate the effects of dietary supplemental vitamin C (VC) on SE challenged-broilers. In experiment 1, one hundred eighty 1-day-old Arbor Acre broilers were randomly allocated into 3 treatments, with 0, 500, or 1,000 mg/kg VC included in the diet. In experiment 2, dietary VC at 0 or 500 mg/kg, with or without SE challenge was applied in a 2 × 2 factorial arrangement in 6 randomized complete blocks. In experiment 1, addition with 500 mg/kg VC increased BW and infectious bursal disease (IBD) titer of broilers on 35 D (P < 0.05), whereas 1,000 mg/kg VC had no effects on the IBD titer (P > 0.05) compared with the control group. In experiment 2, SE challenge depressed BW on 11 and 21 D (P < 0.05 and P = 0.088, respectively), whereas increased mortality and hepatic bacterial translocation (P < 0.05) on 21 D. Further, SE challenge resulted in lower villus height in jejunum, lower microbial richness, and diversity, whereas higher abundance of Enterobacteriaceae in cecum (P < 0.05). Importantly, supplementation with VC increased BW on both 21 and 35 D (P < 0.05 and P = 0.088, respectively) and enhanced the intestinal health by improving villus morphology and microbial structure as indicated by higher cecal microbial richness and Firmicutes to Bacteroidetes ratio, while lower abundance of Enterobacteriaceae (P < 0.05). In addition, birds fed with 500 mg/kg VC in the diet had significantly increased jejunal secretory immunoglobulin A levels, T lymphocytes stimulation index, and serum total antioxidant capability compared with groups without VC (P < 0.05). In conclusion, SE challenge induced lower production performance and higher mortality in broilers. However, dietary supplementation with VC ameliorated SE-caused damage in broilers by improving the intestinal health, partly mediated by shaping the structure of cecal microbiota.